Vaccine prophylaxis: achievements, problems, perspectives of development. - Mavrutenkov, V. V.; Revenko, G. O. (Medicni Perspektivi, 2016)
The article presents medical and social aspects of immune prophylaxis of infectious diseases; the history of vaccines and vaccination is presented, as well as perspectives of development of vaccine prophylaxis.